Multifaceted implementation of stroke prevention guidelines in primary care: cluster-randomised evaluation of clinical and cost effectiveness. Issue 1 (14th February 2007) - Wright, John; Bibby, John; Eastham, Joe; Harrison, Stephen; McGeorge, Maureen; Patterson, Chris; Price, Nick; Russell, Daphne; Russell, Ian; Small, Neil; Walsh, Matt; Young, John
Abstract : Objective: To evaluate clinical and cost effectiveness of implementing evidence-based guidelines for the prevention of stroke. Design: Cluster-randomised trial Setting: Three primary care organisations in the North of England covering a population of 400 000. Participants: Seventy six primary care teams in four clusters: North, South & West, City I and City II. Intervention: Guidelines for the management of patients with atrial fibrillation and transient ischaemic attack (TIA) were developed and implemented using a multifaceted approach including evidence-based recommendations, audit and feedback, interactive educational sessions, patient prompts and outreach visits. Outcomes: Identification and appropriate treatment of patients with atrial fibrillation or TIA, and cost effectiveness. Results: Implementation led to 36% increase (95% CI 4% to 78%) in diagnosis of atrial fibrillation, and improved treatment of TIA (odds ratio of complying with guidelines 1.8; 95% CI 1.1 to 2.8). Combined analysis of atrial fibrillation and TIA estimates that compliance was significantly greater (OR 1.46 95% CI 1.10 to 1.94) in the condition for which practices had received the implementation programme. The development and implementation of guidelines cost less than £1500 per practice. The estimated costs per quality-adjusted life year gained by patients with atrial fibrillation or TIA were both less than £2000, very much less than the usual criterion for cost effectiveness. Conclusions: Implementation of evidence-based guidelines improved the quality of primary care for atrial fibrillation and TIA. The intervention was feasible and very cost effective. Key components of the model include contextual analysis, strong professional support, clear recommendations based on robust evidence, simplicity of adoption, good communication and use of established networks and opinion leaders.